Análisis para la estructuración organizacional y comercial de la empresa rodamientos y repuestos Giro S.A.S. - Rodríguez Ramírez, Cristhian Camilo; Nossa Arias, Enrique; Henao Restrepo, José Antonio (Corporación Universitaria Minuto de Dios, 2020)
Con este análisis se pretende evaluar la empresa con la finalidad de diseñar y desarrollar un orden jerárquico dentro de la institución, estableciendo funciones para cada cargo al interior de la empresa ajustadas a las necesidades actuales, desarrollando su respectivo manual de funciones, el mismo que permitirá tener una idea más clara de las actividades y responsabilidades a desempeñar; por otro lado, la investigación realizada fue 5 de tipo científica de campo utilizando el método inductivo dinámico el mismo que permitió observar los hechos bajo una meta concreta previamente definida; debido a la circunstancia actual mundial hubo que modificar la forma de recopilar información, interpretar, comprobar y analizar las causas del fenómeno; como población y muestra del estudio se tomó agentes internos y externos comprendidos por 10 empleados y 90 integrantes de los proveedores internacionales y clientes nacionales; los instrumentos estadísticos aplicados fueron encuestas al gerente, empleados, clientes y proveedores, con dichos resultados se comprobó la hipótesis con un porcentaje de aceptación de 90%, que consiste en el diseño de una estructura organizacional y funcional que permitirá mejorar el posicionamiento de la empresa en el mercado, conocer el nivel de aceptación de la propuesta planteada, contribuyendo a la optimización de procesos, recursos humanos y materiales para una adecuada toma de decisiones.

The purpose of this research is to carry out an organizational and commercial diagnosis in the sector of auto parts companies in the city of Ibagué. For this, different methods of data collection were applied between interviews, direct observation and documentary analysis, with the information obtained being evidenced that the companies in the spare parts sector lack an organizational scheme and commercial strategies that allow them to position themselves in the market in a competitive way. In order to strengthen the business competitiveness of the sector and to structure the empirical processes of these small entrepreneurs, this project was developed taking as a sample the company Repuestos y Rodamientos GIRO SAS, entity dedicated to the commercialization of spare parts in the automotive and agro-industrial sector, Analyzing the internal and external factors of the organization, which allows observing the aspects in favor and the elements that negatively influence its correct operation. The primary objective of this project is to structure the company in its organizational area and implement a commercial strategy that allows it to grow and position itself in the auto parts market, contributing to the economic and social development of the region. This analysis aims to evaluate the company in order to design and develop a hierarchical order within the institution, establishing functions for each position within the company adjusted to current needs, developing its respective functions manual, which will allow have a clearer idea of the activities and responsibilities to carry out; on the other hand, the research carried out was of a scientific field type using the dynamic inductive 7 method, which allowed observing the facts under a previously defined concrete goal; Due to the current world circumstance, the way of collecting information, interpreting, checking and analyzing the causes of the phenomenon had to be modified; As population and sample of the study, internal and external agents comprised of 10 employees and 90 members of international suppliers and national clients were taken; the statistical instruments applied were surveys of the manager, employees, clients and suppliers, with these results the hypothesis was verified with an acceptance rate of 90%, which consists in the design of an organizational and functional structure that will improve the positioning of the company in the market, to know the level of acceptance of the proposed proposal, contributing to the optimization of processes, human and material resources for adequate decision-making.
Diseñar una estructura organizacional y comercial en la empresa GIRO SAS para mejorar su posicionamiento en el mercado de autopartes de la ciudad de Ibagué en el sector de la comercialización de autopartes y sirva como modelo a los pequeños empresarios del gremio
Keywords: Estructura organizacional; Repuestos; Proyecto; Comercialización; Compentencia empresarial; Organizational structure; Spare parts; Business competition; Marketing; Market